Mergulhos bi-Lipschitz de conjuntos semialgébricos - Prado, Vinícius de Oliveira (2023)
The main purpose of this work is to study the fact that a closed semialgebraic set with dimension k in Rn can be embedded in R2k+1 in a bi-Lipschitz way. After that, using this fact, we show that is possible, under certain conditions, to extend a bi-Lipschitz application to the whole space.